KONTRIBUSI ASURANSI SYARIAH TERHADAP PEREKONOMIAN SYARIAH INDONESIA - Nandra, Andre Syah; Kurniawan, Yova Dwi; Purwanto, Muhammad Aji (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
Sharia insurance activities are not only a business, but also a forum for associations based on the values of solidarity and partiality towards others. The main focus is to help and guarantee customer funds (premiums) so that they are managed as best as possible by the management (mudarib) through the tabarru' contract. Although conflicts can arise in the relationship between the two parties in the implementation of the contract, the consequences of the sharia principles inherent in sharia insurance companies demand consistency in the provision of insurance products to prospective customers, especially in Indonesia. The hope for the future is that sharia insurance companies can really uphold the mandate of the people as best as possible. In the midst of the dynamic development of sharia insurance, the affirmation of sharia principles to the wider community is crucial as clear evidence that the contribution of sharia insurance in the insurance industry in Indonesia has significant substance